A Corporate Wellness Program and Nursing Home Employees' Health - Kernan, Gabriela; Cifuentes, Manuel; Gore, Rebecca; Kriebel, David; Punnett, Laura (Frontiers in Public Health, 2020)
Background: Chronic conditions such as obesity, diabetes, and cardiovascular diseases are highly prevalent among the American working population. Some workplaces provide opportunities for health promotion including education, resources, and encouragement to make healthy life choices. Despite growing popularity of workplace health promotion programs, there is no consensus about their effectiveness. Objective: The aim was to evaluate a company-sponsored workplace health promotion program in the long-term care sector (nursing homes, i.e., residential facilities providing skilled nursing care). We sought to compare the prevalence of various worker health indicators, health beliefs and behaviors, and work environment conditions among facilities that did or did not provide such program support. Methods: Nursing home employees from 18 facilities within a single company were surveyed by a standardized, self-administered questionnaire. We categorized the facilities by level of program development and intensity. Cross-sectional associations were estimated between level of workplace promotion programs and worker health beliefs and behaviors. Results: A total of 1,589 workers participated from 5 broad job categories. Working conditions were mostly similar across centers with different programs, except for significantly higher supervisor and coworker support in centers with well-developed programs. Average Body Mass Index was slightly lower in centers with well-developed and emerging workplace wellness programs. Similarly, regular aerobic exercise outside of working hours was slightly more common in those centers. Conclusions: Only small health benefits were observed from well-developed programs and center-level working conditions did not appear to confound those negative results. The main finding is that a low-intensity, low-resourced workplace health promotion programs may have benefited a few individuals but seem to have had only modest influence on average levels of the measured indicators. More targeted approaches that provide more environmental and economic supports for healthy behaviors may yield larger health benefits.